High- and low-bar squatting techniques during weight-training - Wretenberg, P.; Feng, Y.; Arborelius, U. P. (Medicine & Science in Sports & Exercise, 1996)
Wretenberg et al (1) examined the differences between high-bar (used by Olympic lifters in training) and low-bar (used by powerlifters in training and competition) squatting techniques. They examined differences in moments of force at the knee and hip joints and EMG activity of the vastus lateralis, rectus femoris, and biceps femoris. 8 Swedish national class Olympic weightlifters and 6 Swedish national class powerlifters were used in the study. Weightlifters performed high-bar squats and powerlifters performed low-bar squats; each group of lifters did not perform both types due to lack of skill in the technique that did not correspond with their particular sport. In both groups, 2 depths of squatting were examined: parallel (posterior border of hamstring parallel with ground) and full (knees maximally flexed). All subjects lifted 65% of their all-time 1 RM. Motion analyses were performed using a video camera, with skin markers placed at the trunk, hip, knee, ankle, and foot. Coordinates of the markers were established using a video position analyzer. Ground reaction forces were measured using a Kistler force platform; vertical, anteroposterior, and lateral forces were measured during the ascent phase. Knee and hip joint moments were calculated using a computer program and the data from the markers and the force platform. EMG activity was related to a static reference position to compare muscle activity of both types of squats. A parametric t-test was used as the statistical analysis.